A Thousand Splendid Suns - Hosseini, Khaled (London Bloomsbury, 2007)
Two women born a generation apart witness the destruction of their home and family in war torn Kabul, losses incurred over the course of thirty years that test the limits of their strength and courage.
English Fiction.
Keywords: Afghanistan -- Families -- Loss (Psychology)